2007
DOI: 10.1080/00048670701519864
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Death Associated with Antipsychotic Drug Dispensing in Residential aged Care Facilities

Abstract: The increased risk associated with haloperidol and chlorpromazine dispensing should be interpreted cautiously because confounding by medical illness cannot be excluded despite adjusting the model for multiple variables. This study supports the findings from other data linkage studies that atypical antipsychotic medications are not associated with increased risk of death compared with conventional antipsychotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…911,13,24 No previously conducted study has successfully controlled for all of these factors. For example, a study by Hollis et al 24 inferred comorbidity from prescription drug claims data and was, therefore, unable to measure factors beyond overall morbidity and drug burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…911,13,24 No previously conducted study has successfully controlled for all of these factors. For example, a study by Hollis et al 24 inferred comorbidity from prescription drug claims data and was, therefore, unable to measure factors beyond overall morbidity and drug burden.…”
Section: Discussionmentioning
confidence: 99%
“…911,13,24 No previously conducted study has successfully controlled for all of these factors. For example, a study by Hollis et al 24 inferred comorbidity from prescription drug claims data and was, therefore, unable to measure factors beyond overall morbidity and drug burden. Gill et al 10 and Rochon et al 9 used propensity scores for comorbidity and drug burden, whereas Liperoti et al 13 controlled for several health-related factors (behavior problems, functional status, body mass index, concomitant medications, and comorbidity) using information from the Systematic Assessment of Geriatric Drug Use via Epidemiology database.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional antipsychotics were consistently associated with a 20-40% relative increased risk of death when compared to atypical antipsychotics [22,26-29,31,32,56]. Absolute risks, however, varied between studies according to the method employed to control for confounding.…”
Section: Resultsmentioning
confidence: 99%
“…Absolute risks, however, varied between studies according to the method employed to control for confounding. Conventional statistical methods adjusting for measured covariates suggested an increased risk over 6 months of between 2 and 3 deaths per 100 patients treated with conventional compared to atypical antipsychotics [22,27,56] while those that used an instrumental variable analysis, to adjust for unmeasured confounding, found an increased risk of between 4 and 7 deaths per 100 patients treated over 6 months [28,29] and up to 10 deaths per 100 over 12 months [31]. Only one observational cohort study [26] and one case–control study [23] found no significant difference between the classes.…”
Section: Resultsmentioning
confidence: 99%
“…10,13,31,34,[36][37][38]41,42,47,52 In all nine of these studies, users of conventional antipsychotics had a higher risk of mortality than users of atypical antipsychotics (see Table 2). 10,13,31,34,[36][37][38]41,42,47,52 In all nine of these studies, users of conventional antipsychotics had a higher risk of mortality than users of atypical antipsychotics (see Table 2).…”
Section: Atypical Vs Conventional Apm and All-cause Mortalitymentioning
confidence: 99%